Pengaruh Penerapan Pernyataan Standar Akuntansi Keuangan 109 Terhadap Implementasi Good Governance - Dariana Dariana; Ruzita Ruzita (LPPM ISNJ Bengkalis, 2019)
The purpose of this study was to determine how the application of Financial Accounting Standards Statement 109 and the implementation of Good Governance in the National Zakat Board of Bengkalis Regency and the influence of the application of the Financial Accounting Standard Statement 109 on the implementation of Good Governance in the national zakat board of Bengkalis Regency. This research was conducted using quantitative descriptive methods. These data were obtained from questionnaire data, interviews and documentation that were distributed to all employees of the Bengkalis Regency National Amil Zakat Agency and several Zakat Collection Units in Bengkalis Regency. The analytical method used in this study is to use a simple linear regression. The results of this study indicate that the effect of the adoption of the Statement of Financial Accounting Standards 109 has a positive and significant effect on the implementation of Good Governance by 90.9%.